Meningkatkan kecerdasan kinestetik melalui kegiatan tari kreasi pada anak usia dini - Nunzairina Nunzairina; Alyssia Diva Aziza (At Turots: Jurnal Pendidikan Islam, 2023)
This study has the aim to find out through creative dance activities can improve kinesthetic intelligence in children aged 5-6 years at the Ananda Putri Batang Quiz Integrated Islamic Kindergarten. This study used the PTK method (classroom action research) which consisted of 20 students, namely 10 boys and 10 girls in class B. The percentage before taking the action was called Prasiklus with the results being carried out at the Ananda Putri Islamic Integrated Kindergarten Batang Quiz i.e. 35%. The target set by researchers is 80%. Cycle I increased 70% compared to Pracycle after the action. However, when the results obtained were not in accordance with the objectives, Cycle II was carried out which resulted in an increase in results of 95%. Therefore, this research has been said to be successful. These results are consistent that kinesthetic intelligence in children aged 5-6 years at Ananda Putri Islamic Integrated Kindergarten can be improved through dance creations